RETRACTED: Pengaruh motivasi dan lingkungan kerja terhadap kinerja karyawan PT. Poetra Jaya Sukses Mandiri di Batam - Daulay, Nopitasari; Hikmah, Hikmah (Jurnal Kajian Manajemen Bisnis, 2020)
RETRACTION TO:Daulay, N., & Hikmah, H. (2020). Pengaruh Motivasi dan Lingkungan Kerja Terhadap Kinerja Karyawan PT Poetra Jaya Sukses Mandiri Di Kota Batam. Jurnal Kajian Manajemen Bisnis, 9(1) (doi: https://doi.org/10.24036/jkmb.10806000This article has been retracted by Publisher based on the following reason:The Editor of Jurnal Kajian Manajemen BisnisÂ  found the double publication in the article publishing due to article's content similarity published in http://ijcoreit.org/index.php/coreit/article/view/148Daulay, N., & Hikmah, H. (2020). Pengaruh Motivasi dan Lingkungan Kerja Terhadap Kinerja Karyawan PT Poetra Jaya Sukses Mandiri Di Kota Batam. Jurnal Ilmiah Core IT: Community Research Information Technology, 8(1).One of the conditions of submission of paper for publication in this journal is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. Re-use of any data should be appropriately cited. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission processÂ